2005
DOI: 10.1097/01.mbc.0000169220.00679.13
|View full text |Cite
|
Sign up to set email alerts
|

Low normal level of protein C or of antithrombin increases risk for recurrent cardiovascular events

Abstract: The relationship between haemostatic factors and recurrent cardiovascular events was investigated in patients enrolled with acute coronary syndrome (acute non-Q myocardial infarction or unstable angina pectoris). One hundred and fifteen patients, aged 64 +/- 10 years, were included in the study. Haemostatic parameters [prothrombin time, activities of factor VII, factor VIII, factor X, antithrombin (AT) and protein C (PC), and concentrations of free protein S, fibrinogen, D-dimer, prothrombin fragment 1+2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
2
3
1
Order By: Relevance
“…Only one study has previously investigated the role of antithrombin levels on recurrent ATE in CHD patients. In a prospective cohort study by Pelkonen et al on acute coronary syndrome patients, patients who had a recurrent arterial event had lower antithrombin levels than patients who had no recurrence [19]. However, these subjects were mostly male, and substantially older (64 ± 10 years) than in our study (43.6 ± 5.8 years).…”
Section: Discussioncontrasting
confidence: 67%
See 1 more Smart Citation
“…Only one study has previously investigated the role of antithrombin levels on recurrent ATE in CHD patients. In a prospective cohort study by Pelkonen et al on acute coronary syndrome patients, patients who had a recurrent arterial event had lower antithrombin levels than patients who had no recurrence [19]. However, these subjects were mostly male, and substantially older (64 ± 10 years) than in our study (43.6 ± 5.8 years).…”
Section: Discussioncontrasting
confidence: 67%
“…However, when using antithrombin activity as a binary variable with predefined cut-off of the median antithrombin level, a 46% increased risk of ATE was found in the adjusted analysis for the participants with low antithrombin levels (OR 1.46; 95% CI:1.09e1.96). Similar results were found in the CHD group (OR 1.43; 95% CI:1.01e2.02) and in the IS group (OR 1.48; 95% CI: 1.01e2 19)…”
supporting
confidence: 85%
“…These close associations might help explain clinical observations showing that low normal levels of these 2 inhibitors increase the risk of recurrent cardiovascular events in patients with ACS. 53 Previously, we have shown in this patient population that simulated Tf-initiated thrombin generation based upon factor composition can discriminate between acute and stable CAD. 22 We have also demonstrated that these ACS and CAD MI patients have circulating fXIa that correlates with markers of coagulation and inflammation.…”
Section: Discussionmentioning
confidence: 88%
“…There are several possible explanations for this finding. PAI-1 release has been associated with ischemic cardiovascular disease and heart failure (35,36); lower levels of protein C also are associated with ischemic cardiovascular disease (37)(38)(39). The presence of circulatory shock has been associated with lower levels of protein C in patients with ALI/ARDS (11).…”
Section: Discussionmentioning
confidence: 99%